Rheological properties and compressive properties of alkali-activated slag-fly ash geopolymer fluid solidified soil - Chunxiao Qi; Boshen Wang; AnHui Chen; Haiting Zhang; Shuai Pang (PLoS ONE, 2026)
To study the influence of the content of cementitious materials, water-solid ratio, fiber content and NaOH content on the rheological properties and compressive properties of geopolymer fluid solidified soil, and to reveal the influence mechanism of different factors on geopolymer fluid solidified soil (GFSS). Geopolymers prepared from slag and fly ash were mixed into aeolian soil as cementing materials, and the rheological parameters of GFSS were tested by MCR rheometer, and its compressive strength was tested after curing for 28 days, and its micro-morphology was obtained by SEM. When the content of cementing material is increased from 8% to 16%, the fluidity of GFSS decreased by 62.01 mm and the compressive strength increases by 121.52%. When the water-solid ratio increased from 0.26 to 0.34, the fluidity increased by 81.79%, and the compressive strength first increased and then decreased, reaching the peak when the water-solid ratio was 0.30. With the increase of fiber content, the fluidity will decrease, and the compressive strength will also increase first and then decrease. When the fiber content is 5‰, the fiber will form a stable three-dimensional network structure, and the compressive strength will reach 1.19MPa. With the increase of NaOH content, the fluidity of slurry decreases, the system structure becomes denser and the mechanical properties are significantly improved. When the proportion of NaOH is 6%, cementing material is 12%, water-solid ratio is 0.30, and fiber content is 5‰, the comprehensive performance of GFSS is good, which can meet the application requirements of secondary excavation and backfill engineering. The research results are of great significance for improving the design standard of solidified soil backfill engineering, increasing the service life of solidified soil backfill engineering and reducing the disaster of pavement collapse in seasonal frozen soil areas.